Equity, Efficiency and Sustainability in Water Allocation in the Andes: Trade-offs in a Full World - María Cecilia Roa-García (Water Alternatives, 2014)
Conflicts between water users are increasing, making evident the lack of a judicious, balanced and transparent procedure for water allocation. This is particularly apparent in regions where demand comes from users with a wide range of needs and different levels of power, and where human appropriation of water is reaching unsustainable levels. Allocation mechanisms with varying degrees of governmental intervention exist in Colombia, Ecuador and Peru, and they reflect the priorities that these societies give to relevant normative principles governing water: equity, efficiency and sustainability. Water laws in these three countries indicate that 1) while efficiency has become the bastion of neo-liberalisation, equity and sustainability principles are either neglected or become subsidiary, 2) implicit definitions of equity fall short in promoting the interests of the disadvantaged, and 3) the complex definition, measurement and monitoring of what constitutes a sustainable scale of human water use, make it an impractical goal. Achieving a balance between equity, efficiency and sustainability appears unrealistic, suggesting the need to remove efficiency as a principle in water allocation and make it an important but subsidiary tool to equity and sustainability.